Tofu Dregs Chips Business’ Branding to Increase Sales Potential and Income for MSMEs - Ismawardani, Anjella; Santoso, Slamet; Hamidah, Choirul (International Journal Labs, 2022)
Background: Branding is an identity created by marketing people to make it easier for consumers to choose products. The role and obstacles faced by home industry owners and the strategies carried out by home industry voters in facing existing obstacles. Aim: This study aims to determine the role of branding in the home industry to increase sales potential and community income. Method: This study uses qualitative descriptive research. The source of data was taken in Bringinan Village, Jambon District, Ponorogo Regency, which was raised from the results of the Ormawa Capacity Building Program Fund Grant of the Ministry of Education, Culture, Research, and Technology. Findings: To overcome current challenges, sellers might employ a number of tactics. The Ponorogo Regency Department of Trade, Cooperatives, and MSMEs provides assistance with branding socialization and training so that residents of Bringinan Village in Jambon District are more informed about the significance of branding in the home sector.